Analysis and Assessment of a Brushless DC Outrunner Motor for Agriculture Drones Using JMAG - Javier de la Cruz Soto; Jose J. Gascon-Avalos; Jesse Y. Rumbo-Morales; Gerardo Ortiz-Torres; Manuel A. Zurita-Gil; Felipe D. J. Sorcia-Vázquez; Javier Pérez-Ramírez; Obed A. Valle-López; Susana E. Garcia-Castro; Hector M. Buenabad-Arias; Moises Ramos-Martinez; Maria A. López-Osorio (Applied System Innovation, 2025)
Designing propulsion systems for agricultural drones involves a repetitive process that is both expensive and time-intensive. At the same time, conducting comprehensive experimental tests demands specialized equipment and strict safety protocols. In this work, the design and assessment of the propulsion system (propeller, motor, and battery) for large-sized drones in agricultural applications are conducted using numerical methods. To properly predict and validate the performance of a brushless direct current motor, a three half-bridge inverter circuit, featuring a trapezoidal commutation, is implemented and constructed. First, the propeller is studied using the finite volume method, obtaining a maximum variation of 6.32% for thrust and 10.1% for torque. Additionally, an electromagnetic analysis on a commercial brushless direct current motor (BLDC) using JMAG software from JSOL corporation (JMAG designer 23.2, Cd.Obregón, México) resulted in 4.43% deviation from experimental electrical measurements. The selected propulsion system is implemented in a 30 kg drone, where motor performance is evaluated for two instants of time in a typical agriculture trajectory. The findings demonstrate that numerical methods provide valuable insights in large-sized unmanned aerial vehicle (UAV) design, decreasing the experimental tests conducted and accelerating implementation time.